Phraseology in the film Nine Queens: Manifestation and Translation-oriented analysis of Argentinian Fixed Verbal Constructions (Islas, 2025)
Introduction: The objective is to highlight the numerical importance of diatopic variation in the discipline of phraseology through the identification of the Argentinian fixed verbal constructions of the film Nine Queens (2000), for their subsequent translation-oriented analysis into French and English.Methods: With a broad conception of phraseology, Nine Queens (2000) was examined and subsequently its fixed verbal constructions were selected. The transfer of Argentinian constructions into French and English is analyzed through the audiovisual translation approach.Results: Phraseology is fundamental in the prefabricated oral expression of audiovisual productions, regardless of language or geographical area. Of the 57 fixed verbal constructions identified, 48% correspond fully to Argentinian Spanish. Identifying and understanding them is essential in the translation, but there are limitations that make the translation process difficult.Conclusions: The phraseological and translational analysis of Nine Queens (2000) reveals the enormous diatopic phraseological richness that exists in audiovisual productions. These can be opaque even to the general Spanish-speaking public and their translation implies a certain loss of information.
Keywords: fixed verbal constructions; phraseology; diatopic variation; Argentinian Spanish; audiovisual translation